Adrenal crisis in infants and young children with adrenal insufficiency: Management and prevention - Bizzarri, Carla; Capalbo, Donatella; Wasniewska, Malgorzata Gabriela; Baronio, Federico; Grandone, Anna; Cappa, Marco (Frontiers in Endocrinology, 2023)
Background Despite the optimization of replacement therapy, adrenal crises still represent life-threatening emergencies in many children with adrenal insufficiency. Objective We summarized current standards of clinical practice for adrenal crisis and investigated the prevalence of suspected/incipient adrenal crisis, in relation to different treatment modalities, in a group of children with adrenal insufficiency. Results Fifty-one children were investigated, 41 patients (32 patients <4 yrs and 9 patients > 4 yrs) used quartered non-diluted 10 mg tablets. Two patients <4 years used a micronized weighted formulation obtained from 10 mg tablets. Two patients <4 years used a liquid formulation. Six patients >4 yrs used crushed non-diluted 10 mg tablets. The overall number of episodes of adrenal crises was 7.3/patient/yr in patients <4yrs and 4.9/patient/yr in patients>4 yrs. The mean number of hospital admissions was 0.5/patient/year in children <4 yrs and 0.53/patient/yr in children >4 yrs. There was a wide variability in the individual number of events reported. Both children on therapy with a micronized weighted formulation reported no episode of suspected adrenal crisis during the 6-month observation period. Conclusion Parental education on oral stress dosing and switching to parenteral hydrocortisone when necessary are the essential approaches to prevent adrenal crisis in children.